Properties of l=1 B-1 and B*(2) Mesons - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (Amer Physical Soc, 2007)
This Letter presents the first strong evidence for the resolution of the excited B mesons B-1 and B-2(*) as two separate states in fully reconstructed decays to B+(*())pi(-). The mass of B-1 is measured to be 5720.6 +/- 2.4 +/- 1.4 MeV/c(2) and the mass difference Delta M between B-2* and B-1 is 26.2 +/- 3.1 +/- 0: 9 MeV/c(2), giving the mass of the B-2* as 5746.8 +/- 2.4 +/- 1.7 MeV/c(2). The production rate for B-1 and B-2* mesons is determined to be a fraction (13.9 +/- 1.9 +/- 3.2)% of the production rate of the B+ meson.